Variability of wing venation of the dragonfly. - Yablokov, A. V.; Eatin, V. J.; Pritikina, L. N. (Contributions to Entomology = Beiträge zur Entomologie, 1970)
The variability of the cell number in 35 areas of the wings was studied at three species of dragonflies(Sympetrum danae Sulzer, Leucorrhinia albifrons Burmeister and Lestes sponsa Hansemann) from the vicinity of Moscow. Within the population the cell number of the right wing and the left wing is practically the same. As a rule there is a distinct sexual dimorphism in the cell number of both the fore wings and the hind wings of all the species under consideration (thus future studies of populations of dragonflies should use series of individuals of the same sex). A comparison of the variability of the chosen characteristics within a species indicates the possibility of using these characteristics to accurately define not only the sexual differences but also the differences between the populations. The dragonfly wing proves to be a suitable object for the study of microevolutionary processes in a species as well as for obtaining taxonomical data on any level (Characteristics of population, species, genus or family).